Sex-related differences in clinical characteristics and in-hospital outcomes of patients in acute type A aortic dissection - Lin, Fen; Pan, Qiong; Chen, Yaqin; Peng, Yanchun; Jiang, Fei; Ni, Hong; Lin, Lingyu; Chen, Liangwan; Lin, Yanjuan (BMC surgery, 2024)
The aim of this study was to investigate sex-related differences in the clinical characteristics and hospital outcomes of patients undergoing surgery for acute type A aortic dissection (AAAD). This study was a retrospective study. Patients who underwent surgery for AAAD at the Department of Cardiac Surgery, Fujian Medical University Union Hospital, from January 2014 to March 2023 were consecutively included. Data was extracted from electronic medical records. The primary outcome measure was in-hospital mortality, and secondary outcome measures included new-onset postoperative arrhythmia (POA), acute kidney injury (AKI), hepatic dysfunction, neurological complications, gastrointestinal hemorrhage, ICU length of stay, and hospital length of stay. Patients were divided into two groups based on sex, and data analysis was performed using SPSS 25.0 software. A total of 1137 subjects were included, with 863 males (75.9%) and 274 females (24.1%). There were statistically significant differences in age and BMI between the two groups (P < 0.05). There was no statistically significant difference in the incidence of pain at the onset between the two groups, but chest tightness in females was higher than in males (22.6% vs. 13.8%). Regarding primary outcomes, the in-hospital mortality rate was 11.1% for males and 10.6% for females (P = 0.803). There were no statistically significant differences between the groups in ICU days, length of hospitalization, neurological complications, or liver dysfunction (P > 0.05). The rate of POA in females was 4.7%, higher than in males (2.2%), but AKI and gastrointestinal hemorrhage were both higher in males than in females (P < 0.05). Multivariate analysis showed that age, white blood cell (WBC) counts, lactic acid, operation duration and prolonged mechanical ventilation (PMV) increased the risk of in-hospital mortality in male patients. Hypertension, WBC counts, lactic acid, and PMV increased the risk of in-hospital mortality in female patients. Despite significant baseline characteristic differences between male and female AAAD patients, there were no significant differences in onset symptoms. The in-hospital mortality rates were similar between male and female patients, but the risk factors for in-hospital mortality differed.